Public spending in agricultural education and research in Mexico (1995-2010) - Quiñonez Salcido, Aureola; Travieso Bello, Ana Cecilia (Agricultura, Sociedad y Desarrollo, 2020)
Federal public spending for promotion of the agricultural sector in Mexico during the mid-20th century was characterized by a high public intervention in irrigation infrastructure and modernization of the Mexican farmland. In contrast, at the end of the last century, public transferences were destined mainly to backing the income of farmers. Therefore, this study evaluates the impact of federal agricultural public spending in Mexico and its research and education components, on agricultural growth during 1995-2010. The analysis of the Agriculture Orientation Index revealed that the public sector gave more importance to public transferences of sectors other than agriculture. In addition, a decreasing trend was observed in the participation of the agricultural sector in the economy as a whole. It was found that public transferences destined to the promotion of agriculture return to the sector, increased six-fold in a period of one year; meanwhile the expenditure in agricultural education and science returned hundredfold in a lapse of four years. It is recommended to devote more resources to programs for promotion of agricultural education and research, strengthening productive chains and driving competitiveness and agrifood development.